Urban Bird Feeders Dominated by a Few Species and Individuals - Galbraith, Josie A.; Jones, Darryl N.; Beggs, Jacqueline R.; Parry, Katharina; Stanley, Margaret C. (Frontiers in Ecology and Evolution, 2017)
The practice of garden bird feeding is a global phenomenon, involving millions of people and vast quantities of food annually. Many people engage in the practice of feeding assuming that birds gain some benefit from the food they provide, yet recent studies have revealed the potential for detrimental impacts as well. However, there is still a paucity of information on the impacts of feeding, including the ubiquity of these impacts among and within feeder-visiting species. Consistency in feeder use among birds is likely an important determinant of this. Individual birds and species that make frequent use of feeders are more likely to experience both the benefits and detrimental impacts of supplementary food. We investigated patterns of feeder use by garden birds visiting experimental feeding stations in Auckland, New Zealand, with the specific aim of determining whether use of supplementary food was consistent or variable among individuals and species. We used camera traps as well as Radio Frequency Identification (RFID) technology to examine intra- and interspecific feeder visitation patterns and to discern species associations. Eleven bird species were detected using feeding stations, however, two introduced species (house sparrow Passer domesticus and spotted dove Streptopelia chinensis) dominated visitation events. These species were present at feeders most frequently, with the largest conspecific group sizes. Significant associations were detected among a number of species, suggesting interspecific interactions are important in determining feeder use. We also found within-species differences in feeder use for all focal species, with individual variation greatest in house sparrows. Furthermore, season had an important influence on most visitation parameters. The observed individual and species-specific differences in supplementary food resource use imply that the impacts of garden bird feeding are not universal. Crucially, particularly given the avifaunal context in New Zealand, resource dominance by introduced species could have potential negative outcomes for native species conservation in cities.